Management of hypertension in the digital era: perspectives and future directions - Fujiwara, T; McManus, R; Kario, K (Elsevier, 2022)
Information and communication technology (ICT) have advanced remarkably in recent years. In the field of medicine, the problem of hypertension management seems especially well-suited to the application of novel methods. In patients with hypertension, it is important to assess blood pressure (BP) levels throughout the day and night, along with circadian BP variation, using out-of-office BP monitoring. ICT is an attractive tool to facilitate such monitoring and promises to change the current management of hypertension. The combination of self-telemonitoring of BP with lifestyle modification appears to be effective for strict BP control. ICT could be a solution to the challenging problem of nonadherence to antihypertensive medications and could reduce so-called clinical inertia in the treatment of hypertension. ICT approaches would be especially useful in geographically isolated areas or during natural disasters or complex health emergencies such as the ongoing coronavirus pandemic. However, it will be necessary to develop innovative ICT devices for easy and accurate BP measurement in a range of individuals, including the elderly, and to confirm their effectiveness in large scale clinical trials. ICT-based management of hypertension is expected to be pivotal for reducing the public-health burden of cardiovascular diseases and to be widely adopted in daily clinical practice in the future.